The Effect of Behavioral Counseling with Self-Management Techniques to Reduce Misbehavior Tendencies in Students: A Gender-Based Analysis - Abdul Aziz, Muhammad; Ni Ketut Suarni; Putu Ari Dharmayanti (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The background of this study is the high level of student misbehavior that disrupts the learning process. The tendency of misbehavior can be overcome with the right counseling approach and technique. Behavioral counseling with self-management techniques. The main objective of the study was to analyze the effect of behavioral counseling with self-management techniques in reducing the tendency of misbehavior, and to explore differences in influence based on gender. The type of research used was an experiment with a